Analysis of ancestry informative markers in three main ethnic groups from Ecuador supports a trihybrid origin of Ecuadorians. (November 2017) - Santangelo, Roberta; González-Andrade, Fabricio; Børsting, Claus; Torroni, Antonio; Pereira, Vania; Morling, Niels
Highlights: A total of 162 Ecuadorians (Kichwa, Mestizo, and Afro-Ecuadorian) were investigated with the Precision ID Ancestry Panel. The genetic markers analysed showed higher levels of diversity in Afro-Ecuadorian and Mestizo compared to the Kichwa group. The Kichwa had the highest Native Amerindian (NAM) component of three the ethnic groups studied (91.5% in average). The Mestizo presented an admixed ancestry of NAM and European components, with the latter representing around 30% in average. Afro-Ecuadorian were highly admixed presenting proportions of African, NAM, and European ancestries. Abstract: Ancestry inference is traditionally done using autosomal SNPs that present great allele frequency differences among populations from different geographic regions. These ancestry informative markers (AIMs) are useful for determining the most likely biogeographic ancestry or population of origin of an individual. Due to the growing interest in AIMs and their applicability in different fields, commercial companies have started to develop AIM multiplexes targeted for Massive Parallel Sequencing platforms. This project focused on the study of three main ethnic groups from Ecuador (Kichwa, Mestizo, and Afro-Ecuadorian) using the Precision ID Ancestry panel (Thermo Fisher Scientific). In total, 162 Ecuadorian individuals were investigated. The Afro-Ecuadorian and Mestizo showed higher average genetic diversities compared to the Kichwa. These results are consistent with the highly admixed nature of the first two groups. The Kichwa showed the highest proportion of Native Amerindian (NAM) ancestry relative to the other two groups. The Mestizo had an admixed ancestry of NAM and European with a larger European component, whereas the Afro-Ecuadorian were highly admixed presenting proportions of African, Native Amerindian, and European ancestries. The comparison of our results with previous studies based on uniparental markers (i.e. Y chromosome and mtDNA) highlighted the sex-biased admixture process in the Ecuadorian Mestizo. Overall, the data generated in this work represent one important step to assess the application of ancestry inference in admixed populations in a forensic context.